Challenges of university nursing transfer students in an Asian context: a qualitative study. Issue 5 (15th May 2020) - Ching, Shirley S Y; Zhang, Lillian Weiwei; Guan, Gwendoline Yuanyuan; Cheung, Kin
Abstract : Objectives: To explore the social and academic experiences of nursing transfer students' (NTSs) in an Asian context. Design: A descriptive qualitative study design using focus groups and individual interviews with Chinese NTSs. The data were transcribed verbatim and analysed by using qualitative content analysis. Setting: A university offering preregistration nursing programmes in Hong Kong. Participants: Chinese NTSs studying in a 3-year special pattern within a 5-year Bachelor of Nursing programme in a university in Hong Kong. Results: Four main categories were identified: 'expectations about study at the beginning of the programme', 'challenges during transition', 'coping by prioritising' and 'our world is small'. The NTSs had clear goals for becoming professional nurses and consequently aimed at higher academic achievements throughout the study. They anticipated enjoying university life at the beginning of their study; however, the challenges caused by heavy study workloads and transition from passive to independent learning approaches, compounded by the limited time of 3-year study, forced them to develop coping strategies to reconcile and prioritise their preconceived notions, academic pursuits, social engagements and personal well-being. Their high prioritisation of good academic performance confined their university lives to the small world of the academic arena. Conclusions: The study identified challenges faced by NTSs in adjusting to university study. Suggestions are offered to different stakeholders to address the issues at individual, institutional and government levels so as to enhance NTSs' learning experiences at university.